High rate oxygen reduction reaction during corrosion of ultra-high-purity magnesium - Cheng Wang (Nature Portfolio, 2020)
Abstract Comprehending the corrosion mechanism of magnesium is of major interest in diverse fields. Typically, hydrogen evolution reaction is considered as the only cathodic reaction during Mg corrosion. However, recent works demonstrate importance of considering oxygen reduction reaction (ORR) as a second cathodic process at specific conditions. With oxygen micro-optode, we show that ORR rate was higher on slower corroding ultra-high-purity Mg (UHP-Mg), while lower on faster corroding commercially pure Mg (CP-Mg), where massive hydroxide layer impeded oxygen permeation. These findings shed light on yet another facet of complex mechanism of Mg corrosion.